Cellular Neurothekeoma of the Upper Lip in an Infant - Hsin-Yen Pan; Sheng-Hong Tseng; Chia-Chi Weng; Yun Chen (Elsevier, 2014)
Cellular neurothekeoma is an uncommon benign skin neoplasm and also a variant of neurothekeoma. Cellular neurothekeomas usually occur in the skin of the upper trunk, head, or neck of children and young adults; however, they rarely occur in infants or involve the lip. A 6-month-old male infant was incidentally found to have a tumor in the upper lip. The tumor was elastic, nontender, and movable, and the overlying mucosa and skin were normal without discoloration. The tumor was excised from the mucosal side of the upper lip, and a pathological examination revealed cellular neurothekeoma. Cellular neurothekeoma in the lip of an infant without overlying skin discoloration might delay the diagnosis and lead to wrong preoperative diagnosis. No similar case has been reported in the literature.